Which tongue? The imported colonial standard or motherland vernacular? exploring “death” as the birth of postcolonial Malaysia in Muthammal Palanisamy’s funeral chant - Kavitha Ganesan (University of Hawai'i Press, 2022)
This article examines “death” in a funeral chant set in the plantation estates of Malaysia, and written in English and Tamil, as a metaphor for the birth of the nation. It explores how the death of communal linguistic elements, both in orality and symbolic references, lead to the deconstruction of motherland identity markers which are then replaced by the reconstruction of diasporic identities that are observable through the use of standardized English. For this purpose, the Malaysian Indian life-writer, Muthammal Palanisamy’s English version of an oppari (Tamil for funeral chant), which was published in Malaysia (2002) will be read in relation to the Tamil version published in India (2007) through transliterated and translated texts of the chant. In so doing, the paper highlights the inherent gap between the two versions that can be usefully deployed to address whether English is an enabling tool through which ethnic Indians can express their identities in a postcolonial nation like Malaysia or is it perpetually contaminated by colonial history and values. On the other hand, the paper also draws attention to the question of whether the displacement of the vernacular language, i.e., Tamil, witnesses the inevitable cultural death of a diasporic community or does it display a form of inclusivity within the polyglot linguistic environment of the adopted land, Malaysia.